Some target-firm determinants of premiums in public takeovers : Evidence from the Nordic stock exchanges - Niva, Oskar (My University, 2022)
In this thesis, I focus on investigating and identifying target-firm level determinants of M&A premiums in public takeovers, within the Nordic context. The sample used in this thesis covers 372 takeovers with publicly listed targets in the Nordics, excluding Iceland, between 2006-2021. The tested determinants were picked from recent M&A premium determinant literature, covering the different aspects of target firm characteristics comprehensively. My findings on target firm characteristics’ impact on the takeover premium can be summarized as follows. First, I find that the takeover premiums were significantly affected by two target firm characteristics. In particular, takeover premiums tended to be lower for targets with higher levels of free cash flow and tangible assets. In addition, out of the other examined target firm determinants, target firm’s size impacted the takeover premium negatively and level of intangible assets affected the takeover premium positively. Secondly, I show that target firm’s industry or country does not independently (jointly) impact the takeover premium levels in the Nordcs. These findings are inconsistent with some existing literature (Dombret et al., 2008; Madura et al., 2012). However, some sporadic industries and countries show significance in explaining the takeover premium in the Nordics. Public takeovers with targets in the healthcare sector end up receiving significantly higher takeover premiums. In addition, takeovers with Danish targets generate lower takeover premiums, while takeover with Swedish targets generate greater premiums. Finally, the last aspect I investigate is the country-differences in target firm characteristics and takeover premiums. By applying country-specific interaction terms for the targets in different Nordic countries, I find that some country-specific target firm characteristics have significant power in explaining the takeover premium and the country-differences in them. In particular, target’s level of intangible assets, within takeovers with Finnish targets, does have significant power in explaining the takeover premium. However, as this is blatantly inconsistent with exisiting literature (Laamanen, 2007; Fidrmuc et al., 2012), indicates this, that level of intangible assets with Finnish takeover targets is a key factor in explaining intercountry differences in takeover premiums between the Nordic countries.
Keywords: Yrityskauppapreemio, Yrityskauppapreemion determinantit, Yrityskohtaiset determinanti